2005
DOI: 10.1086/502581
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality, Hospital Stay, and Cost Due to Candidemia: A Case-Control Study Using Data From Population-Based Candidemia Surveillance

Abstract: Our findings underscore the burden of candidemia, particularly regarding the risk of death, length of hospitalization, and cost associated with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
229
2
22

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(257 citation statements)
references
References 27 publications
4
229
2
22
Order By: Relevance
“…Trichosporon was reported as the second most common cause of disseminated yeast infections which can also cause to break through under CAS treatment as in our study [30]. Although catheter removal is recommended after identifying the fungemia, catheter removal by 24 or 48 h after treatment initiation was reported to have no effect on overall treatment response, mortality and mycological eradication in 842 patients with candidemia [31][32][33]. CAS therapy is recommended by ESCMID Fungal Infection Study Group if catheter retention is needed due to clinical conditions of the patient [34].…”
Section: Discussionmentioning
confidence: 54%
“…Trichosporon was reported as the second most common cause of disseminated yeast infections which can also cause to break through under CAS treatment as in our study [30]. Although catheter removal is recommended after identifying the fungemia, catheter removal by 24 or 48 h after treatment initiation was reported to have no effect on overall treatment response, mortality and mycological eradication in 842 patients with candidemia [31][32][33]. CAS therapy is recommended by ESCMID Fungal Infection Study Group if catheter retention is needed due to clinical conditions of the patient [34].…”
Section: Discussionmentioning
confidence: 54%
“…12 Another case-control study found that case-patients receiving adequate treatment for IC had increased length-of-stay (LOS) by 3 to 13 days, as well as $3,000 to $22,000 more in hospital costs compared to controls. 13 This same study found that patients were more likely to die when inadequate candidemia treatment was administered.…”
Section: The Case For Antifungal Stewardshipmentioning
confidence: 88%
“…La mortalidad atribuible a bacteriemias por Acinetobacter baumannii multiresistente en el estudio de NY Lee fue de 21,8% 6 . La mortalidad atribuible a candidemias fue de 24% 9 . Los estudios realizados en neumonía asociada a ventilación mecánica (NAVM), documentaron una mortalidad atribuible variable, de 16% 10 y 7,3% 11 .…”
Section: Discussionunclassified